The Use of Quantitative Sensation Testing to Identify the Physiological Differences Between the Median and Ulnar Nerves - Koszewicz, Magdalena; Szydlo, Mariusz; Gosk, Jerzy; Wieczorek, Malgorzata; Slotwinski, Krzysztof; Budrewicz, Slawomir (Frontiers in Human Neuroscience, 2021)
Introduction: Similarities in morphology, physiological function, and neurophysiological findings between median and ulnar nerves are not unequivocal. Our previous study confirmed differences in motor fiber parameters between these nerves in healthy persons. We made an attempt to assess and compare the physiological parameters of different sensation modalities (temperature, pain, vibration) in median and ulnar nerves. Methods: The study was performed in 31 healthy, right-handed volunteers: 17 women, 14 men, mean age 44.8±15.5 years. Standard sensory conduction tests in the median and ulnar nerves were performed together with the estimation of vibratory, temperature, and warm- and cold-induced pain thresholds in the C7 and C8 dermatomes on the palm, using quantitative sensory testing (QST). Results: There were no statistically significant differences in the standard sensory conduction test in the median and ulnar nerves across the whole group: between right and left hands, and between women and men. We revealed differences in the temperature and pain thresholds between these nerves, mainly in low temperature perception. There were no differences in estimated thresholds between sides or in female and male groups. The vibratory limits did not differ significantly between nerves, and subgroups. Conclusions: The study confirmed the differences in the physiological sensory perception between the median and ulnar nerves. The median nerve is more sensitive to temperature stimulation than the ulnar nerve, but simultaneously less sensitive to pain-inducing temperature stimuli. These findings should be considered during the examination of hand nerve pathology.